Isolation of some microorganisms from Iraqi patients with acute maxillary sinusitis. - Zeiny, Sarmad M.; Al-Salloum, Suhaila M. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: Maxillary sinusitis is one of the most common infections of humans. Sinusitis can be defined as an inflammation of the membrane lining of any sinus, especially one of the paranasal sinuses. Objective: To determine the causative microorganisms of acute maxillary sinusitis. Patients: Forty five acute sinusitis patients were involved in the present study. Methods: Sampling methods were per-oral nasopharyngeal swabs. Results: Haemophilus species, Streptococcus pneumoniae (S.pneumoniae) and Moraxella catarrhalis (M.catarrhalis) were the most frequent isolates. Conclusion: The most causative agents of acute maxillary sinusitis were bacterial isolates, which were Haemophilus species followed by S.pneumoniae and M.catarrhalis. the incidences of acute sinusitis were more common at patients’ age (20-29 years old) groups.